Usefulness of Activated Carbon Prepared from Industrial Wastes in the Removal of Nickel from Aqueous Solution - R. Rajalakshmi; S. Subhashini; P. Lalitha (E-Journal of Chemistry)
Elimination of heavy metals like nickel from waste water is an important subject in view of public health. In the present study, an attempt has been made to study the applicability of industrial by-products as potential metal adsorbents to remove nickel from aqueous solutions and polluted water. A direct proportionality between the percentage of Ni(II) removal and adsorbent dosage was noted. Maximum removal ⁄ recovery of nickel was achieved at pH range of 10-12 for all adsorbents. An optimum temperature of 40 °C for efficient removal of Ni(II) was observed. The effect of nickel adsorption was affected by salinity. The adsorption isotherm data confirmed to Freundlich and Langmuir isotherms. Conformation of data to the Lagergren᾽s rate equation indicated first order kinetics. The suitability of the industrial by-products in the successful removal of nickel from aqueous solution is quite obvious from the study.